Efforts to Improve Learning Activeness of Grade 5 Students Through the Google Meet Application - Haryani, Eka Septi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The background of this research is that online learning is not optimal because it only uses the Whatshapp group and there are still many students who do not submit assignments. The purpose of this study is to describe the use of google meet in order to increase student learning activity in class V SD Negeri Banjaranyar. The research conducted was Classroom Action Research which consisted of planning, implementing, observing and reflecting. In the first cycle the percentage of students was 5% less active, 40% active enough and 55% active students. Whereas in cycle II the percentage of students was quite active 25% and only 75% active students. The percentage of student activeness in cycle III is 95% active students and 5% of students are quite active. This result shows that the use of the google meet application can increase student activity in grade 5 SD Negeri Banjaranyar.